DESAIN JASA PENDIDIKAN PADA MADRASAH IBTIDAIYAH ALAM ISLAMIC CENTER PONOROGO - Nika Rustiani (Muslim Heritage, 2018)
Abstract: This article discuss the description of educational services products, the implications of education services products to the excellent image school and  the strategy of product development of education services at Madrasah Ibtidaiyah Alam Islamic Center Ponorogo. It employed qualitative approach and case study research. The result of analysis showed that First, in creating educational product and program is carried by forming a series of activities including core benefit, basic product, expected product, augmented product, potential product and conducted observation, design product, socialization product, implementation product, evaluation product. Second, the strategy of educational product development services is conducted by changing old products, formulating similar products or programs and rearranging educational products or programs. Thirdly, in realizing its image as a superior school can be seen from three aspects, namely input, process and output. While the implication of education program or product can be carried out through the increasing of customer satisfaction.  Abstrak: Artikel ini akan membahas tentang bagaimana deskripsi produk jasa pendidikan di Madrasah Ibtidaiyah Alam Islamic Center Ponorogo, bagaimana implikasi produk jasa pendidikan terhadap citra madrasah unggul di Madrasah Ibtidaiyah Alam Islamic Center Ponorogo dan bagaimana strategi pengembangan produk jasa pendidikan di Madrasah Ibtidaiyah Alam Islamic Center Ponorogo. Artikel ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Berdasarkan kajian dalam artikel ini, maka dapat disimpulkan: Pertama, Madrasah Ibtidaiyah Alam Islamic Center Ponorogo dalam menciptakan produk atau program pendidikannya dilakukan dengan membentuk rangkaian kegiatan yang meliputi core benefit, basic product, expected product, augmented product, potential product dan melakukan alur observation, design product, socialization product, implementation product, evaluation product. Kedua, strategi pengembangan produk jasa pendidikan di Madrasah Ibtidaiyah Alam Islamic Center Ponorogo dilakukan dengan mengubah produk lama, merumuskan produk atau program yang sejenis dan menata ulang produk atau program pendidikan. Ketiga, Madrasah Ibtidaiyah Alam Islamic Center Ponorogo dalam mewujudkan citranya sebagai madrasah unggul dapat dilihat dari tiga aspek, yaitu input, proses dan output. Sedangkan implikasi produk atau program pendidikan terhadap citra madrasah unggul di Madrasah Ibtidaiyah Alam Islamic Center Ponorogo ini adalah dengan meningkatnya kepuasan pelanggan.